1995
DOI: 10.1128/aac.39.12.2783
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and infection with Enterococcus faecalis in intensive care units: the role of antimicrobial agents

Abstract: We studied the influences of antimicrobial agents on the colonization of the respiratory tract and infection with Enterococcus faecalis in intensive care unit (ICU) patients receiving mechanical respiration for at least 3 days. In a matched-cohort analysis, patients receiving topical antimicrobial prophylaxis (TAP) of the oropharynx and stomach with antimicrobial agents not treating E. faecalis were compared with patients not receiving TAP. Patients were matched with controls on the basis of their duration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 30 publications
0
10
2
1
Order By: Relevance
“…Few data are available for comparison. Bonten et al (2) demonstrated in a study from 1995 that 16% of patients admitted to an ICU were colonized with E. faecalis in the oropharynx and/or trachea at admission. The higher initial rate of E. faecalis colonization in the present study (55%) might be due to the fact that the time point for admission and intubation sometimes do not coincide.…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available for comparison. Bonten et al (2) demonstrated in a study from 1995 that 16% of patients admitted to an ICU were colonized with E. faecalis in the oropharynx and/or trachea at admission. The higher initial rate of E. faecalis colonization in the present study (55%) might be due to the fact that the time point for admission and intubation sometimes do not coincide.…”
Section: Discussionmentioning
confidence: 99%
“…Feeley et al [7] have found just a single case (0.3%) of pneumonia caused by E. faecalis among 292 patients in an intensive-care unit, who received polymyxin B aerosol in an attempt to prevent P. aeruginosa pneumonia; That patient had died, but the manuscript did not discuss the attribution of the pneumonia to his mortality. Bonten et al [8] reported of 6 patients with ventilator-associated pneumonia, in which E. faecalis had presumably taken a major etiologic role. These patients were part of a group of 61 patients, whose ages ranged from 58 to 79 years, who were given topical antimicrobial prophylaxis for the oropharynx and stomach; E. faecalis, accompanied by another pathogen in each case, was found in cultures obtained by protected-specimen-brush technique and bronchoalveolar lavage.…”
Section: Burden Of Diseasementioning
confidence: 98%
“…This bacterium, especially E. faecalis (the predominant species isolated from our treated mice), is a major concern in critical care settings, both due to its pathogenicity and to concern regarding antibiotic resistance (6,7,35,40). Enterococcus is well adapted to survival along the mucosa: it can adhere to different epithelial and extracellular matrix proteins (13) and survive in a broad range of pH environments (29).…”
Section: Discussionmentioning
confidence: 99%